Three‐dimensional assessment of impingement risk in geometrically parameterised hips compared with clinical measures - Cooper, Robert J.; Mengoni, Marlène; Groves, Dawn; Williams, Sophie; Bankes, Marcus J.K.; Robinson, Philip; Jones, Alison C. (International journal for numerical methods in biomedical engineering, 2017)
Abnormal bony morphology is a factor implicated in hip joint soft tissue damage and an increased lifetime risk of osteoarthritis. Standard 2‐dimensional radiographic measurements for diagnosis of hip deformities, such as cam deformities on the femoral neck, do not capture the full joint geometry and are not indicative of symptomatic damage. In this study, a 3‐dimensional geometric parameterisation system was developed to capture key variations in the femur and acetabulum of subjects with clinically diagnosed cam deformity. The parameterisation was performed for computed tomography scans of 20 patients (10 female and 10 male). Novel quantitative measures of cam deformity were taken and used to assess differences in morphological deformities between males and females. The parametric surfaces matched the more detailed, segmented hip bone geometry with low fitting error. The quantitative severity measures captured both the size and the position of cams and distinguished between cam and control femurs. The precision of the measures was sufficient to identify differences between subjects that could not be seen with the sole use of 2‐dimensional imaging. In particular, cams were found to be more superiorly located in males than in females. As well as providing a means to distinguish between subjects more clearly, the new geometric hip parameterisation facilitates the flexible and rapid generation of a range of realistic hip geometries including cams. When combined with material property models, these stratified cam shapes can be used for further assessment of the effect of the geometric variation under impingement conditions. This work generated a geometric parameterisation system for the capture cam deformity of the hip joint and quantification of impingement risk. Parametric surfaces and novel 3‐dimensional deformity measures were generated for 20 patients clinically diagnosed with cam impingement. The method was precise enough to demonstrate that cams in males were more superiorly located than in females, a finding that could not be derived from standard clinical 2‐dimensional imaging.